(untitled) (Research, Society and Development, 2025)
The gut microbiota plays a key role in maintaining the body’s homeostasis and actively participates in the communication between the gastrointestinal system and the central nervous system, forming the gut-brain axis. Alterations in its composition, defined as dysbiosis, have been associated with various conditions, including anxiety, depression, autism, and Alzheimer’s disease. In this context, probiotics have emerged as a therapeutic alternative due to their ability to restore microbial balance, modulate inflammation, improve the intestinal barrier, and positively influence neurotransmitter production. This study aimed to analyze, through a literature review, the effectiveness of probiotics in regulating the gut-brain axis and their contribution to the management of psychocognitive disorders. Several strains, such as Lactobacillus rhamnosus, Bifidobacterium longum, and B. breve, have shown positive effects on behavioral and cognitive parameters, indicating the potential of psychobiotics as adjuvants in mental health interventions. However, results in humans still present methodological limitations, requiring more robust studies.